Predictors of Non-Communicable Disease Risk Factors Among People Living with HIV and HIV-Negative Patients in a Nigerian Tertiary Hospital - Noel NB; Banwat ME; Okoro LN; Bulus NG; Nkala CAL; Anyamene EL; Isiko I (HIV/AIDS: Research and Palliative Care, 2025)
Nathaniel Birdling Noel,1 Mathilda Edmund Banwat,2 Lenz Nwachinemere Okoro,3 Naya Gadzama Bulus,4 Chibuzo Anne-Lise Nkala,5 Ebuka Louis Anyamene,6 Isaac Isiko7,8 1Department of Public Health, Modibbo Adama University Teaching Hospital, Yola, Adamawa, Nigeria; 2Department of Community Medicine, University of Jos and Jos University Teaching Hospital, Jos, Plateau, Nigeria; 3Department of Community Medicine, David Umahi Federal University Teaching Hospital, Uburu, Ebonyi, Nigeria; 4Department of Community Medicine, College of Medical Sciences, Abubakar Tafawa Balewa University, Bauchi, Bauchi, Nigeria; 5Johns Hopkins Center for Communication Programs, Breakthrough ACTION Nigeria, Jos, Plateau, Nigeria; 6College of Medicine, University of Nigeria, Enugu, Enugu, Nigeria; 7School of Medicine, College of Health Sciences, Makerere University, Kampala, Uganda; 8Department of Community Medicine, Axel Pries Institute of Public Health and Biomedical Sciences, Nims University, Jaipur, Rajasthan, IndiaCorrespondence: Isaac Isiko, Email isaacisiko12@gmail.comPurpose: In recent years, People Living with HIV (PLHIV) in sub-Saharan Africa have experienced a growing burden of non-communicable diseases (NCDs), straining already limited health systems. Identifying behavioural risk factors for NCDs in both PLHIV and HIV-negative individuals is essential for designing targeted interventions. This study aimed to identify common risk factors for NCDs in these groups and determine their predictors.Patients and Methods: A comparative cross-sectional study was conducted among 250 PLHIV and 250 age- and sex-matched HIV-negative individuals attending the Antiretroviral Therapy (ART) and General Out-Patient clinics of Jos University Teaching Hospital from March 1– 12, 2021. Participants aged 18– 65 years were enrolled. Data were collected using a semi-structured questionnaire and blood pressure measurements. Multivariable logistic regression was used to identify predictors of behavioural risk factors while adjusting for potential confounders.Results: While both groups had similar age and gender distributions, significant differences were observed in education level, marital status, employment, residence, income, ethnicity, and household size (p< 0.05). Among PLHIV, long-term ART use reduced smoking by 93%. In HIV-negative individuals, urban residence and non-harmful alcohol use reduced smoking by 94% and 99%, respectively. Problematic alcohol use was significantly lower in women and non-smokers among PLHIV and HIV-negative individuals, respectively. Low physical activity was associated with poor self-rated health status in both groups, with gender and age playing additional roles among PLHIV and HIV-negative participants, respectively. Among the HIV-negative, unhealthy diets were linked to lower income.Conclusion: Predictors of behavioural risk factors among PLHIV included ART duration, gender, and self-rated health. In the HIV-negative group, age, gender, residence, income, and self-rated health were key predictors. The notable overlap between smoking and alcohol use underscores the need for integrated interventions targeting these behaviours in both populations.Keywords: non-communicable disease, risk factors, PLHIV, HIV-negative, predictors of non-communicable diseases